INFLUENCE OF NEGATIVE PEER PRESSURE AND SUBSTANCE ABUSE ON ANTISOCIAL BEHAVIOUR - Yusuf, Kemi Agana; Alhassan, Emmanuel Onu; Abubakar, Suleiman Aliyu; Daniel, Enoch; Babayo, Sulaiman (African Journal of Social and Behavioural Sciences, 2025)
This study examined the influence of negative peer pressure and substance abuse on antisocial behavior among secondary school students in Lafia, Nasarawa State. A sample of two hundred and twenty (220) secondary school students was used for the study. The participants’ age range was 12 to 18 years old, comprising 46% females and 54% males, with a mean age of 27.1 and a standard deviation of 7.3. The participants were administered the WHO Youth Drug Survey, Peer Influence Scale Questionnaire-Revised, and Subtypes of Antisocial Behavior Questionnaire employing the survey research design and multiple linear regression for data analysis. The first hypothesis was accepted, indicating a significant prediction between negative peer pressure and antisocial behaviour among secondary school students in Lafia, Nasarawa State, Nigeria. The second hypothesis was accepted indicating a significant prediction between substance abuse and antisocial behaviour among secondary school students in Lafia, Nasarawa State, Nigeria. The third hypothesis was also accepted indicating a joint significant prediction between negative peer pressure and substance abuse on antisocial behaviour. It is therefore recommended that government should include counselling services in all the schools in Nigeria that will counsel and educate students on the effects of negative peer pressure and substance abuse on antisocial behaviour.